Systemic Steroid Treatment for Severe Expanding Pneumococcal Pneumonia - Eran Lavi; David Shoseyov; Natalia Simanovsky; Rebecca Brooks (Case Reports in Pediatrics)
The treatment of bacterial community-acquired pneumonia (CAP) is based on appropriate antibiotic therapy and supportive care such as intravenous fluids and supplemental oxygen. There is no available data regarding the use of steroids in CAP in children. We present an unusual case of a child with severe respiratory distress, on the brink of mechanical ventilation, due to a rapidly expanding pneumococcal pneumonia. The administration of systemic steroids resulted in a dramatic response with rapid improvement of clinical and radiological abnormalities followed by improvement of laboratory abnormalities. This case report should raise the awareness of the potential benefits of steroids in the treatment of severe pneumonia in children. Prospective randomized trials are needed to confirm the efficacy of steroids in this setting and to determine which patients would benefit most from this.